Development of a myoelectric interface for indirect hand grip force and wrist angle measurement/analysis - Haja Mohideen, Ahmad Jazlan; Sidek, Shahrul Na'im (IIUM Press, International Islamic University Malaysia, 2017)
Limb loss is a growing problem due to the increasing number of accidents worldwide. A cybernetic prosthesis is a device which can assist individuals with hand disabilities by enabling them to have some of the hand capabilities of an able bodied individual. Extracting hand grip force and wrist angle information from forearm electromyogram (EMG) signals is useful to be used as inputs for the control of cybernetic prostheses. By establishing the relationship between forearm EMG and hand grip force/wrist angles, the prosthetic hand can be controlled in a manner that is customised to an amputee’s intent. In this research work, a myoelectric interface which consists of an electronic conditioning circuit to measure EMG signals and software to record and process the EMG signals were developed. Experimental training and testing datasets from five subjects were collected to investigate the relationship between forearm EMG, hand grip force and wrist angle simultaneously.